In Search of Project Management Efficiency : Renewal of Public Sector Institutions - Lichtarski, Janusz Marek; Stańczyk-Hugiet, Ewa; Wąsowicz, Marek (W poszukiwaniu efektywności zarządzania projektami : odnowa organizacyjna w sektorze instytucji publicznych, 2010)
The authors present a research proposal that concerns project management efficiency in the public sector institutions and the model of their project management advancement. Efficiency of project management determines quantity and quality of results. The high PM efficiency means better results in a proper time and with adequate costs. This is a crucial matter for the public sector institutions, which exist to accomplish goals and tasks for the society. Taking those aspects into consideration, the present research proposal seems to concern a very important and up-to-date issue. The purpose of the following research project is to improve the understanding of organizational renewal possibilities by efficient project management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 215-225
Keywords: public sector; project management maturity; project management efficiency; renewal